2020
DOI: 10.3390/cells9061558
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Cardiac Stem Cell Senescence to Treat Cardiac Aging and Disease

Abstract: Adult stem/progenitor are a small population of cells that reside in tissue-specific niches and possess the potential to differentiate in all cell types of the organ in which they operate. Adult stem cells are implicated with the homeostasis, regeneration, and aging of all tissues. Tissue-specific adult stem cell senescence has emerged as an attractive theory for the decline in mammalian tissue and organ function during aging. Cardiac aging, in particular, manifests as functional tissue degeneration that leads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 248 publications
2
82
0
2
Order By: Relevance
“…In this scenario, an intriguing possibility is that, as CHIP originates in the HSPC compartment, resulting from HSPC clones with DNA mutations conferring them a proliferation/survival-advantage (precancerous clonal expansion), similar mutations could influence senescence, apoptosis and/or differentiation, resulting in dysfunctional tissue-specific adult stem cells contributing to cardiovascular pathology and disease. Of note, the adult mammal heart harbors resident cardiac stem/progenitor cells (CSCs) that contribute to cardiovascular pathology with age [ 94 , 95 , 96 ]. Thus, CHIP could influence and modulate the processes of cardiovascular tissue repair/regeneration of the adult heart and vasculature by affecting the immune modulation of resident stem cells and yielding a pro-fibrotic inflammatory response over reparative/regenerative tissue re-shaping.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this scenario, an intriguing possibility is that, as CHIP originates in the HSPC compartment, resulting from HSPC clones with DNA mutations conferring them a proliferation/survival-advantage (precancerous clonal expansion), similar mutations could influence senescence, apoptosis and/or differentiation, resulting in dysfunctional tissue-specific adult stem cells contributing to cardiovascular pathology and disease. Of note, the adult mammal heart harbors resident cardiac stem/progenitor cells (CSCs) that contribute to cardiovascular pathology with age [ 94 , 95 , 96 ]. Thus, CHIP could influence and modulate the processes of cardiovascular tissue repair/regeneration of the adult heart and vasculature by affecting the immune modulation of resident stem cells and yielding a pro-fibrotic inflammatory response over reparative/regenerative tissue re-shaping.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…This view widens our perspectives on the interplay between ageing, CHIP and CVD risk. In fact, ageing causes cellular and molecular changes in tissue homeostasis, and it is associated with telomere shortening as well as with a multi-component senescence-associated secretory phenotype (SASP), displaying pro-inflammatory cytokines, chemokines, extracellular matrix (ECM)-degrading proteins and other cell-cycle arrest signaling molecules [ 94 , 95 , 96 , 97 ]. All the above factors result in the progressive deterioration of the structure and function of any given organ at the tissue and cell levels [ 97 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…CSCs exposed to statins show a pronounced commitment to myogenesis through a balanced and very robust upregulation of myogenic transcription factors and ensuing expression of sarcomeric genes. These effects raise the potential for a similar effect on senescent CSCs in aging, where both CSC growth and differentiation are significantly impaired [3,[51][52][53][54][55]. The effects of acute exposure to statins both in vitro and in vivo remains to be shown.…”
Section: Discussionmentioning
confidence: 99%
“…Their data showed ALDH2 enzyme increased adverse cardiac remodeling and dysfunction with aging by the AMPK/SIRT1-mediated mitochondrial damage [ 15 ]. Cianflone et al reported that adult cardiac stem cells (CSC) senescence is associated with a decline in myocardial tissue repair [ 16 ]. CSC Senescence is represented by its replicative limit, which is mainly determined by telomere shortening, proper regulation of p53/p16INK4/Rb molecular pathways, chromatin remodeling [ 16 ].…”
Section: Reviewmentioning
confidence: 99%